2018
DOI: 10.1088/1361-6463/aac376
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of electrostatic boundary conditions in gate-patterned quantum devices

Abstract: In a model of a gate-patterned quantum device it is important to choose the correct electrostatic boundary conditions (BCs) in order to match experiment. In this study, we model gated-patterned devices in doped and undoped GaAs heterostructures for a variety of BCs. The best match is obtained for an unconstrained surface between the gates, with a dielectric region above it and a frozen layer of surface charge, together with a very deep back boundary. Experimentally, we find a ∼ 0.2 V offset in pinch-off charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…m * indicates the effective electron mass in a GaAs crystal. Here we obtain U (y) for the specific geometry of the presently investigated device by solving the corresponding Poisson problem 42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…m * indicates the effective electron mass in a GaAs crystal. Here we obtain U (y) for the specific geometry of the presently investigated device by solving the corresponding Poisson problem 42,43 .…”
Section: Resultsmentioning
confidence: 99%
“…The blue curve in Fig. S6 shows the conduction band along the SAW-propagation direction (the x axis), where the source (electron) bias V source = −0.8 V, the drain (hole) bias V drain = 0.65 V, and the side-gate voltage V SiG = −0.4 V. This calculation of the electrostatic potential, based on the real device geometry, was carried out using the partial differential equation solver Nextnano [1,2]. As can be seen, the potential difference between the region of electrons (left) and the region of holes (right) is about 80 meV, so electrons cannot overcome this potential difference and recombine with holes unless a SAW drags these electrons to the region of holes.…”
Section: S7 Modelling Of Saw-driven Charge Transportmentioning
confidence: 99%
“…This approach makes it possible to create multiple synchronised single-photon sources at chosen positions with photon energy determined by quantum-well thickness. Compared with conventional quantum-dot-based single-photon sources, this device may be more suitable for an on-chip integrated photonic quantum network.The development of single-photon sources is important for many quantum information technologies [1][2][3], such as quantum cryptography [4][5][6], quantum communication [7][8][9], quantum metrology [10, 11], and quantum computation [12, 13]. Currently, most high-performance single-photon sources are self-assembled InGaAs-based quantum dots (QDs) [14][15][16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the model and experiments, we have shown that this boundary condition is inappropriate as charges in dangling bonds there become frozen at cryogenic temperatures, and a deep boundary condition in the GaAs substrate gives more accurate results, and indeed we have shown that it is essential in calculations for an undoped device. 24 Figure 3(g) shows the calculated electrostatic potential energy in an induced n-i-n junction matching the experimental design. The junction entrance presents a potential slope of ∼ 20-30 meV/µm, which the SAW is expected to be able to overcome with applied SAW power above 10 − 15 dBm, 25,26 comparable to our experimental results in figure 2.…”
mentioning
confidence: 79%